Measuring the Eating Habits of Registered Dietitians. Issue 3 (July 2015) - Schumacher, Sarah; Davis, Anne
<x xml:space="preserve">Abstract</x> Registered dietitian/nutritionists (RDNs) are educated with a minimum of a bachelor of science degree in nutrition/dietetics and trained to teach the dietary guidelines. It is plausible that RDNs incorporate the dietary guidelines into their lifestyles. The aim of this study was to answer the question, "do Wisconsin RDNs ≥ 21 years old who adhere > 90% of the 2010 Dietary Guidelines (DGs) have lower body mass indexes (BMIs) compared to RDNs who adhere to < 90% of the DGs?" A cross-sectional study design included an electronic survey of 1100 Wisconsin RDNs using the Healthy Eating Index–2010 (HEI-2010) as the measurement tool. Seven percent of RDNs completed the study. The mean BMI was 24.16 ± 4.12 kg/m2 (SD) with a mean HEI-2010 score of 80.08 ± 11.28 (SD); a weak, significant negative correlation (r = −0.23, P = .04, slope = −0.08) was found between BMI and HEI scores of all RDNs. Those who adhered to greater than 90% of 2010 DG recommendations had corresponding lower BMIs than those registered dietitians not following greater than 90% of the DG's recommendations.